Customer Complaint Service Business Processes Redesign with Artificial Intelligence Technology Using Business Process Reengineering Approach (Study Case: Ceria BRI Application) - Sissy Soraya Faradilla; Sugeng Santoso (Indonesian Journal of Business Analytics, 2024)
This article analyses the business process redesign of Ceria BRI's customer complaint service using Artificial Intelligence (AI) technology with Business Process Reengineering (BPR) approach. This qualitative research with a post-positivism paradigm reveals that making complaints at Ceria BRI currently uses several channels such as telephone, email, social media, and applications. The problems faced include the high number of complaints that received every month in 2023, and some complaints were resolved over Service Level Agreement (SLA). The proposed solution is to redesign the proposed business process design by applying the four stages of Business Process Reengineering (BPR), namely Visioning-Identifying-Analyzing-Redesigning. These steps aim to improve service quality, grow positive interactions with customers, and enhance the internal performance of the Ceria BRI customer complaint service team.